Two-Dimensional Models of Cultural Differences: Statistical and Theoretical Analysis. (April 2023) - Fog, Agner
This study finds a common statistical pattern in all major quantitative studies of cultural differences, and discusses theories that explain this pattern. 92 cultural variables from 33 published cross-cultural studies including 125 countries are analyzed with an advanced factor analysis method. The study confirms previous findings that two factors can account for a large part of the variation in all major published cultural variables. While many previously published cultural variables represent arbitrarily rotated factor analysis results, the present study is improving the explanatory power by un-rotating the factors and by incorporating new theories that link cultural values to conditions in the physical and social environment. The first factor, accounting for 34% of the total variance, reflects general effects of development and welfare. This factor is explained by theories of development, modernization, emancipation, and secularization. This includes psychological effects of collective security that are explained by evolutionary psychology. The dimension formed by the first factor has one end in poor and war-torn countries, and the opposite end in North European welfare states. The second factor, accounting for 15% of the total variance, reflects relational mobility, long-term versus short-term orientation, differences in self-construal, and various other effects. Theoretical explanations of these effects are based on differences in subsistence economy, colonial history, ethnic diversity, and religion. The second factor has one end in East Asian countries, and the opposite end in Latin American countries. Analysis of business culture reveals the same two-factor pattern as national culture.